Development of Professional Terminological Competence among Students (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article investigates current issues existing in the modern higher education as well as harmonization thereof with the international and European educational integration processes. Professional and glossary competence development of future professionals is caused by cognitive processes in the today scientific knowledge. The contemporary society expects the professional training to assure certain competences required for the prominent progress in the professional activity. The investigated issue has many aspects, as far as it includes various components related both to internal condition and internal definitiveness of the future professional, his professional fulfillment and professional development, and to his ability to receive and to absorb the knowledge successfully for its further practical implementation, using the creative approach in such cases. When studying terminology it is necessary to take into consideration the fact that the knowledge is systemic by its nature. Systemic nature of the scientific knowledge is displayed in conceptual framework. Systemic nature is more typical for the terminology in comparison with other layers of lexis. The professional activity in any branch requires not only professional skills from the expert, but a comprehensive all-round education, as far as this activity is related to intensive verbal and written communications; it comprises a good speech practice, requires the exact expression of notions and categories. Simulation of the situations similar to various professional situations assures professional orientation of the training process, promotes students’ communicative skills and professional speech progress, upgrades the future professionals’ interest in the terminology study, and provides the possibility to arrange the proper environment for the knowledge practical use. It is reasonable to use creative tasks during classes, which assumes the student’s certain independence during the execution thereof. Such works will help the students to avoid any mindless use of ready patterns during professional literature translation and professional texts writing, encourages them to standard terminology lexical items and professional phraseological term combinations use.
Keywords: professional and glossary competence; scientific terminology; professional vocabulary; systemic character of terminology; structural-cognitive and linguistic-pragmatic aspects